Role of Women in India’s Informal Economy: Opportunities and Challenges (International Journal of Food and Nutritional Sciences, 2024)
The informal economy in India accounts for a significant share of employment, especially for women, who often find limited access to formal workspaces due to socio-economic and structural barriers. This paper examines the critical role women play in India’s informal economy, particularly in sectors such as agriculture, domestic work, street vending, and home-based industries. While this sector offers flexible employment opportunities and serves as a survival strategy for many, it is also characterized by low wages, job insecurity, lack of social protection, and poor working conditions. Through secondary data analysis, field observations, and select case studies, the study explores the dual nature of informal work for women—as both a space of economic participation and exploitation. The paper also highlights the impact of government schemes like MGNREGA and SHG-linked microfinance in enhancing women’s visibility and economic agency. It concludes by recommending policy measures to formalize informal workspaces, ensure decent working conditions, and integrate women workers into India’s broader SDG agenda, especially SDG 5 and SDG 8.